Polyester films and packaging materials
By adopting alternating laminated structures and adding inorganic particles in the polyester film, the noise problem of the polyester film during use is solved, and the balance of biodegradable, low noise, transparency and mechanical strength is achieved, which is suitable for packaging materials.
Patent Information
- Application Number
- JP2023145662
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2023-09-07
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2043-09-07
AI Technical Summary
Existing polyester films produce large noise during use, affecting their commercial application, especially in packaging materials that require transparency and biodegradability.
A polyester film with an alternating laminate structure is adopted, wherein the first layer contains lactic acid residue and the second layer contains television acid residue and agolic acid residue. By adjusting the layer thickness ratio and adding inorganic particles, noise is reduced and transparency and mechanical strength is maintained.
The biodegradable polyester film has been improved in low noise, transparency and mechanical strength, and is suitable for packaging materials, especially food packaging and disposable products.
Smart Images

Figure 0007624485000003 
Figure 0007624485000004 
Figure 0007624485000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a packaging material using a biodegradable polyester film having an improved noise level. [Background technology]
[0002] Polylactide resin is known as an environmentally friendly material that can be recycled because it biodegrades within a relatively short period of time, leaving behind almost no harmful components.
[0003] However, when such polylactide resins are processed into a film for use, they emit very loud noises, which has acted as a limitation in practical commercialization.
[0004] To overcome these shortcomings of polylactide resin, there is a method of blending polylactic acid with an aliphatic-aromatic copolymer polyester to impart flexibility to the film. However, in this case, due to factors such as the low compatibility between polylactic acid and aliphatic-aromatic copolymer polyester, the transparency of the final film is significantly reduced, making it difficult to use for packaging applications that require transparency.
[0005] The above-mentioned background art is technical information possessed by the inventor for the purpose of deriving the present invention or acquired in the process of deriving the present invention, and is not necessarily publicly known art that was disclosed to the general public prior to the filing of the application of the present invention.
[0006] Related prior art includes Korean Patent No. 10-0904144 (Patent Document 1) and Korean Patent No. 10-2404216 (Patent Document 2). Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the embodiment is to provide a polyester film having improved noise properties, transparency, and biodegradable properties.An object of the embodiment is to provide a packaging material including the polyester film. [Means for solving the problem]
[0008] One embodiment of the present invention provides a polyester film including a laminate of alternating first layers including lactic acid residues and second layers including terephthalate residues and adipic acid residues.
[0009] The polyester film of the embodiment has an average equivalent sound intensity of 78 dB or less in an evaluation of film noise intensity when rotated 180 degrees at 800 rpm for 30 seconds or more.
[0010] The Young's modulus of the polyester film of the embodiment is 280 kgf / mm 2 It may be the following.
[0011] In the polyester film of the embodiment, when the thickness of the laminate is 16 μm, the film noise level may be 63 dB or less at 250 Hz in the film noise level evaluation.
[0012] The laminate may have a haze of 10% or less.
[0013] According to an embodiment, the polyester film may have a haze of 10% or less.
[0014] In the polyester film of the embodiment, when the thickness of the laminate is 16 μm, the film noise level may be 53 dB or less at 500 Hz in the film noise level evaluation.
[0015] The laminate may be one in which 30 or more of the first layers and the second layers are alternately laminated.
[0016] The first layer may further comprise hydroxyalkanoate residues.
[0017] The first layer may contain 1 to 7 parts by weight of the hydroxyalkanoate residue based on 100 parts by weight of the lactic acid residue.
[0018] The second layer may include a polybutylene adipate co-terephthalate resin.
[0019] The thickness ratio of the first layer to the second layer may be 1:0.2 to 1.5.
[0020] The polyester film of the embodiment may further include a skin layer.
[0021] The skin layers may be disposed on one side and the other side of the laminate, respectively.
[0022] The skin layer can include a first resin that includes lactic acid residues, and inorganic particles.
[0023] The polyester film of the embodiment includes a laminate of a first layer including a lactic acid residue and a second layer including a terephthalate residue and an adipic acid residue, which are alternately laminated. When the film noise level is evaluated by rotating the polyester film 180 degrees at 800 rpm for 30 seconds or more, the polyester film may have a noise level of 80 dB or less at 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, 4000 Hz, and 8000 Hz.
[0024] Another embodiment of the present invention provides a packaging material including the polyester film described above.
[0025] The packaging may be a food packaging or a disposable product packaging. Effect of the Invention
[0026] The embodiment may provide a polyester film that is biodegradable and reduces noise generation. The embodiment may provide a polyester film that is environmentally friendly, relatively transparent, and has appropriate levels of mechanical strength and flexibility while reducing noise generation in the human audible range, especially in the low frequency range, and a packaging material using the same. [Brief description of the drawings]
[0027] [Figure 1] FIG. 2 is a schematic cross-sectional view illustrating an example of a polyester film according to an embodiment. [Figure 2A] FIG. 2 is a schematic cross-sectional view illustrating an example of a polyester film according to an embodiment. [Figure 2B] FIG. 2 is a schematic cross-sectional view illustrating an example of a polyester film according to an embodiment. [Diagram 3] 1 is a conceptual diagram illustrating a noise measurement method applied to evaluation of a noise level in an embodiment; BEST MODE FOR CARRYING OUT THEINVENTION
[0028] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS In the following, embodiments will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily carry out the present invention. However, the embodiments may be embodied in various different forms and are not limited to the embodiments described herein. The same reference numerals are used throughout the specification to refer to similar parts.
[0029] As used herein, the term "combinations thereof" contained in a Markush form expression means a mixture or combination of one or more selected from the group of components set forth in the Markush form expression, and is meant to include one or more selected from the group of components.
[0030] In this specification, the phrase "A and / or B" means "A, B, or A and B."
[0031] Throughout this specification, terms such as "first" and "second" are used to distinguish identical terms from one another, and singular expressions include plural expressions unless the context clearly indicates otherwise.
[0032] In this specification, ppm is based on weight unless otherwise specified.
[0033] The drawings may be presented with exaggerated or simplified configurations for the purpose of explanation, and this should not be interpreted as limiting the scope of the embodiments.
[0034] Polylactic acid resin, a representative biodegradable polymer, has been attracting attention as a film material to replace existing petroleum-based polyester films. However, films using polylactic acid resin generate a relatively loud crackling sound during use, which is sometimes pointed out as a drawback that prevents the film from being used as a packaging material. In particular, when a film containing polylactic acid resin is used as a food packaging material closely related to daily life, such as a bag for confectionery or bread, the crackling sound can act as a noise that causes an unpleasant sensation to the user.
[0035] Noise has become a social problem, so much so that it is called noise pollution, and is something that must be reduced. In addition, because consumers are reluctant to choose products that generate unnecessarily loud noises, it is important to provide biodegradable films that do not generate unnecessary noise, so that they can replace existing petrochemical-based films for environmental reasons.
[0036] The inventors have made various attempts to manufacture a film that has biodegradable properties while at the same time generating low levels of noise, and as a result, present the following examples. Through the examples, the inventors have confirmed that biodegradable polyester films are excellent for use as packaging materials for food, etc., by reducing the generation of rustling sounds and obtaining a certain level of mechanical strength, and present the following examples.
[0037] 1, 2A, and 2B are schematic diagrams illustrating a cross section of an example of a polyester film according to an embodiment, and FIG. 3 is a schematic diagram illustrating a noise measurement method applied to evaluate the noise level of the embodiment. Hereinafter, the embodiment will be described in more detail with reference to FIGS. 1 to 3.
[0038] One embodiment of a polyester film 100 includes a laminate 50 of alternating first layers 52 containing lactic acid residues and second layers 54 containing terephthalate and adipic acid residues (see FIG. 1).
[0039] Another embodiment of the polyester film 100 includes the laminate 50 described above and a skin layer 70 disposed on one or both sides of the laminate (see FIGS. 2A and 2B).
[0040] Laminate The laminate 50 is a laminate in which first and second layers containing distinct polymer resins are alternately laminated.
[0041] The first layer 52 includes lactic acid residues.
[0042] The first layer 52 may include a polylactic acid based resin (PLA based resin).
[0043] Unlike petroleum-based resins, polylactic acid resins are based on biomass, which helps reduce carbon dioxide emissions. They are also biodegradable and decompose faster than petroleum-based resins due to moisture and microorganisms when buried, making them environmentally friendly.
[0044] The polylactic acid resin may be contained in the first layer at 50% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, 93% by weight or more, 95% by weight or more, or 97% by weight or more, or at most 99.9% by weight or at most 99% by weight.
[0045] The polylactic acid resin can contain L-lactic acid residues, D-lactic acid residues, D,L-lactic acid residues, or a combination thereof.
[0046] The content of L-lactic acid residues in the polylactic acid resin may be 80 mol% or more, 83 mol% or more, 85 mol% or more, 88 mol% or more, 90 mol% or more, or 92 mol% or more based on the entire polylactic acid resin. The content of L-lactic acid may be 99 mol% or less, 97 mol% or less, 95 mol% or less, or 93 mol% or less. In this case, the heat resistance of the film can be further improved.
[0047] The content of D-lactic acid residues in the polylactic acid resin may be more than 0 mol%, 0.5 mol% or more, or 1 mol% or more based on the entire polylactic acid resin. The content of D-lactic acid may be 5 mol% or less, or 3 mol% or less. In this case, the stretching processability of the film can be further improved.
[0048] The polylactic acid resin may have a weight average molecular weight (Mw) of 100,000 to 1,000,000 g / mol, for example, 100,000 to 800,000 g / mol, 100,000 to 500,000 g / mol, or 100,000 to 300,000 g / mol. The weight average molecular weight (Mw) can be measured by gel permeation chromatography (GPC). When the weight average molecular weight (Mw) of the polylactic acid resin satisfies the above range, it can be useful for improving the mechanical properties of the film.
[0049] The first layer 52 may further include hydroxyalkanoate residues.
[0050] The hydroxyalkanoate residues may be derived from a polyhydroxyalkanoates resin (PHA resin).
[0051] The first layer 52 may include a polylactic acid resin and a polyhydroxyalkanoate resin.
[0052] Polyhydroxyalkanoate resins are semi-crystalline thermoplastic polyester compounds that can be produced chemically or by microorganisms (bacteria or algae) and are used to make biodegradable plastics.
[0053] The polyhydroxyalkanoate resin may comprise one or more residues selected from the group consisting of poly[3-hydroxybutyrate] (P3-HB); poly[4-hydroxybutyrate] (P4-HB); poly[3-hydroxyvalerate] (PHV); poly[3-hydroxybutyrate]-co-poly[3-hydroxyvalerate] (PHBV); poly[3-hydroxyhexanoate] (PHC); poly[3-hydroxyheptanoate] (PHH); poly[3-hydroxyoctanoate] (PHO); poly[3-hydroxynonanoate] (PHN); poly[3-hydroxydecanoate] (PHD); poly[3-hydroxydodecanoate] (PHDD); and poly[3-hydroxytetradecanoate] (PHTD).
[0054] Specifically, the polyhydroxyalkanoate resin may contain any one selected from the group consisting of 3-hydroxybutyrate residues (3HB residues), 4-hydroxybutyrate residues (4HB residues), and combinations thereof.
[0055] The polyhydroxyalkanoate resin may contain 50 mol % or more, 55 mol % or more, or 60 mol % or more of 3HB residues based on the entire polyhydroxyalkanoate resin, and may contain 100 mol % or less, 80 mol % or less, or 70 mol % or less of said residues.
[0056] The polyhydroxyalkanoate resin may contain 50 mol % or less, 45 mol % or less, or 40 mol % or less of 4HB residues based on the entire polyhydroxyalkanoate resin, or 0 mol % or more, 20 mol % or more, or 30 mol % or more of said residues.
[0057] The polyhydroxyalkanoate resin may contain both 4HB and 3HB residues, and may contain 30 mol% to 35 mol% of 4HB residues based on the entire polyhydroxyalkanoate resin, which may help to control the crystallinity of the film and improve mechanical properties.
[0058] The first layer 52 may be manufactured using a resin obtained by blending the polylactic acid resin and the polyhydroxyalkanoate resin, which may contribute to imparting a certain level of biodegradability and suitable mechanical properties to the polyester film.
[0059] The hydroxyalkanoate residues contained in the first layer 52 may be 1 to 7 parts by weight, or 2 to 6 parts by weight, based on 100 parts by weight of the lactic acid residues. When a resin having such residues in such a range is used, it can provide strength to the film and help control the crystallinity during biaxial stretching, and it can adjust the physical properties of the relatively hard first layer to provide a film with reduced overall noise.
[0060] The resin applied to the first layer 52 may have a melt viscosity at 210° C. of 5,000 P or more or 7,000 P or more, and may be 14,000 P or less or 12,000 P or less. In this case, stable workability can be achieved when manufacturing a laminate by an extrusion method.
[0061] The first layer 52 may further include inorganic particles, which may act as an anti-blocking agent, for example, but are not limited thereto.
[0062] The inorganic particles applied to the first layer are, for example, silica (SiO 2 ), calcium carbonate (CaCO 3 ), indium tin oxide (ITO), aluminum hydroxide (Al 2 (OH) 3 ), zinc oxide (ZnO), titanium dioxide (TiO 2 ), or barium sulfate (BaSO 4 ).
[0063] The inorganic particles may have a D50 of 1 μm or more, or 1.5 μm or more. The D50 may be 3 μm or less, or 2 μm or less.
[0064] The inorganic particles may be contained in the first layer or the skin layer in an amount of 2,000 ppm or less, or 1,500 ppm or less based on the total amount of each layer. When the inorganic particles are contained in the skin layer, they may function as an anti-blocking agent.
[0065] Also, if the first layer contains inorganic particles including calcium carbonate, this can help reduce the noise generation of the polyester film.
[0066] The first layer 52 may further include conventional static charge applying agents, antistatic agents, antioxidants, heat stabilizers, UV blocking agents, antiblocking agents, or combinations thereof, as necessary.
[0067] The second layer 54 includes terephthalate residues and adipic acid residues.
[0068] The second layer 54 is mainly composed of an aliphatic-aromatic copolymer polyester resin, and specifically contains adipic acid residues and terephthalate residues.
[0069] The aliphatic-aromatic copolymerized polyester resin may contain an aliphatic dicarboxylic acid residue, which is adipic acid, and an aromatic dicarboxylic acid residue, which is terephthalic acid, and may further contain a glycol residue.
[0070] The aliphatic dicarboxylic acid may further include, for example, succinic acid, sebacic acid, glutaric acid, malonic acid, oxalic acid, azelaic acid, or nonanedicarboxylic acid.
[0071] The aromatic dicarboxylic acid may further include, for example, isophthalic acid, naphthalene-2,6-dicarboxylic acid, diphenylsulfonic acid dicarboxylic acid, diphenylether dicarboxylic acid, diphenoxyethane dicarboxylic acid, or cyclohexane dicarboxylic acid.
[0072] The glycol residue may be any one selected from the group consisting of alkylene glycols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, propylene glycol, neopentyl glycol, 2-methyl-1,3-propanediol, diethylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, polyethylene glycol, and mixtures thereof.
[0073] The resin contained in the second layer 54 may have an aliphatic component content of 30 mol % or more, 40 mol % or more, 45 mol % or more, or 50 mol % or more based on the total acid components. The aliphatic component content may be 80 mol % or less, 70 mol % or less, or 60 mol % or less based on the total acid components. In this case, the biodegradability of the polyester film can be further improved.
[0074] The resin applied to the second layer 54 may be, for example, polybutylene adipate terephthalate (PBAT) resin, which may help reduce noise levels and improve workability during the manufacturing process of the film.
[0075] The resin applied to the second layer 54 may have a melt viscosity at 210° C. of 3,000 P or more or 4,000 P or more, and may be 9,000 P or less or 7,000 P or less. In this case, stable workability can be achieved when manufacturing a laminate by an extrusion method.
[0076] The aliphatic-aromatic copolymerized polyester resin may have a weight average molecular weight (Mw) of, for example, 50,000 to 400,000 g / mol, 50,000 to 300,000 g / mol, 50,000 to 200,000 g / mol, or 50,000 to 100,000 g / mol. The weight average molecular weight (Mw) can be measured by gel permeation chromatography (GPC). In this case, the resin has excellent compatibility with the resin applied to the first layer and excellent processability.
[0077] The second layer 54 may further include conventional static charge applying agents, antistatic agents, antioxidants, heat stabilizers, UV blocking agents, antiblocking agents, or combinations thereof, as required.
[0078] The second layer 54 has the characteristic of being flexible as compared to the first layer 52 .
[0079] A relatively hard first layer and a relatively soft second layer are alternately laminated to form a laminate 50. The first layer allows the mechanical properties of the entire laminate to be maintained at a certain level or higher, and the interaction between the first and second layers reduces noise generation during use of the film. In particular, a film can be provided that has a significantly reduced equivalent sound pressure level and sound pressure level in the low frequency band compared to polylactic acid films.
[0080] In addition, the optical properties of the polyester film can be improved by laminating multiple layers of the laminate, and in particular, the haze value is lower than that of a film formed as a single layer by blending the resin applied to the first layer and the resin applied to the second layer. Therefore, the embodiment can provide a film with excellent light transmittance in visible light.
[0081] The total number of layers of the laminate 50 may be 4 or more, 6 or more, 10 or more, 30 or more, 34 or more, or 36 or more. The laminate may have 424 or less, 324 or less, or 224 or less. The total number of layers of the laminate is determined based on the number of layers determined assuming that the first layer of the laminate exists when the same resin as that of the first layer is applied to a skin layer described later, making it difficult to distinguish between the first layer of the laminate and the skin layer adjacent to it.
[0082] The laminate 50 has a multi-layer structure in which first layers 52 and second layers 54 are alternately laminated, thereby allowing the polyester film to maintain an appropriate level of mechanical strength while providing a multi-layer polyester film with improved noise levels.
[0083] The laminate may be one in which the first layers and the second layers are alternately laminated in 36 or more layers, or may be one in which 36 to 144 layers are alternately laminated. In this case, it is possible to substantially reduce noise generated when the polyester film is used for general bags such as snack bags.
[0084] In the laminate 50, the ratio of the average thickness of the first layer 52 to the second layer 54 may be 1:0.2-1.5. The ratio of the average thickness of the first layer to the second layer may be 1:0.3-1.3. When the ratio of the average thickness of each of the first layer and the second layer satisfies the above range, it is possible to obtain a noise reduction effect while maintaining an appropriate level or higher of film strength.
[0085] The laminate 50 has the characteristic of being environmentally friendly since it is substantially completely biodegradable over a certain period of time in an environment where microorganisms and moisture are present.
[0086] The laminate 50 may have an average equivalent noise intensity of 78 dB or less in a film noise intensity evaluation in which a 180 degree rotation is applied at 800 rpm for 30 seconds or more. The average equivalent noise intensity may be 77.5 dB or less, 76 dB or less, 74.5 dB or less, or 73 dB or less. The average equivalent noise intensity may be 72 dB or more.
[0087] The film noise level was evaluated using a noise analyzer 14. The sample film (or laminate) for measurement is cut to A4 size, and the long end of the sample is held and fixed by a fixing part 12 (e.g., a jig) to a bar 10 placed in a box that blocks external noise, and the film noise is generated by rotating the bar. The distance d between the tip where the measurement part of the noise analyzer is placed and the film is about 10 cm. The noise level is measured by rotating the bar 180 degrees at a speed of 800 RPM, and the rotation continues for 30 seconds or more (see FIG. 3).
[0088] For example, a film cut to A4 size is prepared in a 650(W)×450(D)×500(H)mm polycarbonate box, and a digital noise analyzer (model: CR-162C) from Cirrus Research PLC is placed in the box (see FIG. 3). The noise analyzer is positioned about 10cm away from the prepared film, and the film is held by a jig at both ends, rotated 180 degrees, and 800 RPM to emit noise for 30 seconds or more to measure the noise. Data analysis is based on the application of the NoiseTools Software program. The program can be used to evaluate the sound intensity and equivalent sound intensity for 30 seconds at each specific frequency. For example, sound intensity and equivalent sound intensity can be measured in the range of 31.5Hz to 16,000Hz.
[0089] The evaluation of the average equivalent noise intensity is based on a value measured when the laminate or the polyester film is at a thickness selected from the range of 15 μm to 30 μm.
[0090] The laminate 50 may have a noise level of 63 dB or less, 62 dB or less, 61 dB or less, or 60 dB or less at 250 Hz in the film noise level rating when the laminate has a thickness of 16 μm, which means that the laminate has a relatively low noise level at frequencies that indicate low tones.
[0091] When the laminate 50 has a thickness of 16 μm, the film noise intensity rating may be 53 dB or less, 52 dB or less, 51 dB or less, or 50 dB or less at 500 Hz. This means that the noise intensity of the relatively low frequency range that people find noisy is low.
[0092] The laminate 50 may have a film noise intensity rating of 59 dB or less, 57 dB or less, 56 dB or less, or 55 dB or less at 1,000 Hz when the laminate has a thickness of 16 μm, which means that the noise intensity in the relatively low frequency range is low.
[0093] The laminate 50 may have a film noise intensity rating of 67 dB or less, 66 dB or less, 65 dB or less, 64 dB or less, or 63.5 dB or less at 2,000 Hz when the laminate has a thickness of 16 μm, which means that the noise intensity is substantially reduced at a frequency that is generally perceived as loud by humans.
[0094] The laminate 50 may have a film noise intensity rating of 75 dB or less, 74 dB or less, 73 dB or less, 72 dB or less, or 71 dB or less at 4,000 Hz when the laminate has a thickness of 16 μm, which means that the noise intensity is substantially reduced in the frequency range where people generally perceive the film as loud and where the loudest noise is generated by the film.
[0095] The laminate 50 may be 72 dB or less, 71 dB or less, 70.5 dB or less, 70 dB or less, 69 dB or less, or 68 dB or less at 8,000 Hz when the laminate has a thickness of 16 μm, which means that there is a reduction in the generation of relatively high-pitched noise.
[0096] Laminate 50 may be 63 dB or less, 62 dB or less, 60 dB or less, or 58 dB or less at 16,000 Hz when the laminate has a thickness of 16 μm, which means that there is a reduction in the generation of high pitched noise.
[0097] The laminate 50 may have a haze of 10% or less, 9% or less, or 8% or less. The haze may be 2% or more, or 4% or more. This is a sufficient level of haze value for application as a packaging material with suitable optical properties, and is particularly excellent compared to a simple blend of a resin having a lactic acid residue and an aliphatic-aromatic copolymer polyester resin. When the two resins are simply blended, the resin becomes cloudy due to poor compatibility between the two resins. In the embodiment, by applying a laminate structure, it is possible to suppress the deterioration of optical properties caused by poor compatibility between the two resins and obtain excellent optical properties. The haze is based on a value measured using a hazemeter (model name: SEP-H) manufactured by Nihon Seimitsu Kogaku.
[0098] Skin Layer The polyester film 100 of the embodiment may further include a skin layer 70 .
[0099] A skin layer 70 may be disposed on one side or the other of the laminate (see FIG. 2A).
[0100] Skin layers 70 may be disposed on one and the other sides of the laminate (see FIG. 2B).
[0101] The skin layer 70 may be made of the resin of the first layer 52. The skin layer 70 may be made of the resin of the second layer 54. In such a case, the manufacturing workability of the polyester film can be further improved, and biodegradable properties can be imparted to the entire film.
[0102] When the resin of the first layer is applied to the skin layer 70, the mechanical properties and workability of the polyester film can be further improved.
[0103] As described above, the skin layer 70 can contain inorganic particles, similar to the first layer, and additives can be applied as necessary.
[0104] The thickness of the skin layer 70 may be applied at a ratio of 5 to 25 based on the thickness 100 of the laminate 50. The thickness of the skin layer 70 may be 0.8 μm or more, 1.2 μm or more, or 2 μm or more, with no particular upper limit to the thickness.
[0105] If the skin layers are applied to both the top and bottom of the laminate, the thickness of the skin layers mentioned above refers to the thickness of one of the skin layers.
[0106] When the skin layer 70 is applied to the polyester film 100, a film having excellent surface strength and controlled overall touch and slip resistance can be provided.
[0107] Polyester Film The polyester film 100 according to the embodiment may have an average equivalent noise intensity of 78 dB or less in a film noise intensity evaluation performed by rotating 180 degrees at 800 rpm for 30 seconds or more. The average equivalent noise intensity may be 77.5 dB or less, 76 dB or less, 74.5 dB or less, or 73 dB or less. The average equivalent noise intensity may be 72 dB or more.
[0108] For example, when measurements are taken under the same measurement conditions for a thickness of about 25 μm, the average equivalent noise intensity of a typical polyester film based on petroleum-based materials is about 80.3 dB, while the average equivalent noise intensity of a polyester film using polylactide resin is at a level of about 83 to 85 dB, so there is a difference.
[0109] The average equivalent sound intensity of the embodiment substantially suppresses or reduces noise generation even though a biodegradable polymer such as polylactic acid resin is used. That is, the embodiment can provide a biodegradable polyester film that suppresses noise more than polyester films (based on petroleum-based materials) used as product packaging materials.
[0110] The evaluation of the average equivalent noise intensity or the evaluation of the noise intensity is based on a value measured when the laminate or the polyester film is at a thickness selected from the range of 10 μm to 30 μm.
[0111] The polyester film 100 according to the embodiment may have a noise level of 63 dB or less, 62 dB or less, 61 dB or less, or 60 dB or less at 250 Hz in the film noise level evaluation, which means that the film has a relatively low noise level at a frequency that indicates low sound.
[0112] The polyester film 100 according to the embodiment may have a noise level of 53 dB or less, 52 dB or less, 51 dB or less, or 50 dB or less at 500 Hz in the film noise level evaluation, which means that the noise level of the relatively low frequency range that people find noisy is low.
[0113] The polyester film 100 according to the embodiment may have a film noise level of 59 dB or less, 57 dB or less, 56 dB or less, or 55 dB or less at 1,000 Hz in the film noise level evaluation, which means that the noise level in a relatively low frequency range is low.
[0114] The polyester film 100 of the embodiment may have a film noise level of 67 dB or less, 66 dB or less, 65 dB or less, 64 dB or less, or 63.5 dB or less at 2,000 Hz in terms of the film noise level evaluation. This means that the noise level is substantially reduced in terms of the frequency of noise that is generally perceived as loud by humans.
[0115] The polyester film 100 of the embodiment may have a film noise level of 75 dB or less, 74 dB or less, 73 dB or less, 72 dB or less, or 71 dB or less at 4,000 Hz in the film noise level evaluation. This means that the noise level is substantially reduced in the region where the film generates the loudest noise, which is a frequency that is generally perceived as loud by humans.
[0116] The polyester film 100 of the embodiment may have a noise level of 72 dB or less, 71 dB or less, 70.5 dB or less, 70 dB or less, 69 dB or less, or 68 dB or less at 8,000 Hz, which means that the generation of relatively high-pitched noise is reduced.
[0117] The polyester film 100 of the embodiment may have a noise level of 63 dB or less, 62 dB or less, 60 dB or less, or 58 dB or less at 16,000 Hz, which means that the generation of high-pitched noise is reduced.
[0118] The polyester film may have a haze of 10% or less. The polyester film may have a haze of 6.5% or more and 9.5% or less. The polyester film may have a haze of 7% or more and 9% or less. When the polyester film has a haze within the above ranges, transparency is ensured, and the film may be used in various applications requiring translucency. The haze was measured using a haze meter (model name: SEP-H) manufactured by Nihon Seimitsu Kogaku.
[0119] The polyester film 100 of the embodiment has a Young's modulus of 280 kgf / mm 2 The Young's modulus is based on a value measured in accordance with ASTM D882, and refers to an average Young's modulus which is an average value between the MD direction, which is the machine direction, and the TD direction, which is the transverse direction, of the film.
[0120] The Young's modulus is 280 kgf / mm 2 Below, 275kgf / mm 2Below, 270kgf / mm 2 Below, 220kgf / mm 2 Below 200kgf / mm 2 or less than 160kgf / mm 2 The Young's modulus may be 80 kgf / mm 2 Over 100kgf / mm 2 More than 120kgf / mm 2 Above, 125kgf / mm 2 or more, or 150kgf / mm 2 Young's modulus is one of the indices showing the flexibility of a polyester film, and a flexible film is sometimes considered to generate less noise, but the results of repeated experiments by the inventors show that there is not necessarily a certain correlation between the level of Young's modulus and the level of noise generated by the film. However, it does indicate that the film has more flexible properties overall.
[0121] The polyester film 100 of the embodiment has a tensile strength of 3 kgf / mm 2 More than 4kgf / mm 2 More than 5kgf / mm 2 or more than 7kgf / mm 2 or more, 17kgf / mm 2 Below, 15kgf / mm 2 or less than 12kgf / mm 2 The polyester film may have a tensile strength suitable for use as a packaging material. When the tensile strength in the MD direction is different from that in the TD direction, the tensile strength means an average value of the tensile strength in the MD direction and the TD direction.
[0122] The polyester film 100 of the embodiment may have an elongation of 60% or more, 70% or more, or 75% or more, or may have an elongation of 120% or less. When the elongations in the MD and TD directions are different, the elongations refer to their average values. The polyester film may have elongation properties suitable for use as a packaging material.
[0123] The polyester film 100 of the embodiment may have a heat shrinkage rate of 5% or less, 4% or less, or 3% or less. The heat shrinkage rate may be 0.5% or more. This means that the polyester film has dimensional stability above a certain level, and the embodiment may have stable heat shrinkage rate characteristics.
[0124] The polyester film 100 of the embodiment may have a thickness of 1,000 μm or less, 800 μm or less, 600 μm or less, 400 μm or less, 200 μm or less, 100 μm or less, or 60 μm or less. The thickness may be 10 μm or more, or 15 μm or more. In this case, it may have a thickness suitable for use as a packaging material.
[0125] The polyester film 100 of the embodiment includes a laminate of a first layer including a lactic acid residue and a second layer including a terephthalate residue and an adipic acid residue, and the polyester film 100 may have a noise level of 80 dB or less, 77 dB or less, or 75 dB or less when the film noise level is evaluated by applying a 180° rotation at 800 rpm for 30 seconds or more, where the noise levels are values measured at 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, 4000 Hz, and 8000 Hz, respectively.
[0126] The polyester film 100 has low noise levels across a wide range of frequencies from low to high that are primarily perceived by humans, and thus can provide a polyester film that is environmentally friendly and relatively quiet while having a certain level of mechanical strength.
[0127] Manufacturing method of polyester film A method for producing a polyester film according to another embodiment includes the steps of preparing a composition, obtaining an unstretched sheet, and obtaining a polyester film.
[0128] The composition preparation step is a step of preparing a first resin composition containing a lactic acid residue and a second resin composition containing a terephthalate residue and an adipic acid residue (hereinafter referred to as a first step).
[0129] The step of obtaining an unstretched sheet is a step of melt-extruding the first resin composition and the second resin composition, respectively, to obtain an unstretched sheet including a laminate in which a first layer containing the first resin and a second layer containing the second resin are alternately laminated (hereinafter referred to as the second step).
[0130] The step of obtaining a polyester film is a step of stretching the laminated sheets and heat fixing them to obtain a polyester film (hereinafter, referred to as the third step).
[0131] The specific description of the polyester film and the laminate is the same as that given above, and therefore will not be repeated here.
[0132] The first resin composition may include the above-mentioned resin for the first layer, inorganic particles, additives, etc. The second resin composition may include the above-mentioned resin for the second layer, additives, etc.
[0133] The melt viscosities of the resin of the first layer and the resin of the second layer at 210°C are as described above, and when resins having such melt viscosities are used for the first resin composition and the second resin composition, it is advantageous to manufacture a laminate by applying an extrusion method.
[0134] The first resin composition and the second resin composition may be subjected to a step of removing moisture in the first step and / or the second step, and the moisture content may be adjusted to 150 ppm or less.
[0135] The second step may be applied with a conventional film lamination means such as a feed block. Exemplarily, the film lamination means may have a structure capable of discharging molten resins corresponding to the first layer and the second layer so as to be laminated, and may further include a portion into which the resin of the skin layer is discharged. When the first resin composition or the second resin composition is applied to the skin layer, the workability can be further improved. The thickness ratio of each layer of the laminate and the thickness ratio of the skin layer can be controlled by controlling the amount of the molten resin discharged, for example.
[0136] The thickness ratio and the like are as described above, and the thickness of each layer can be controlled in consideration of the stretching step described below and the like.
[0137] In the second step, the unstretched sheet can be formed into a sheet by a process such as bringing the unstretched sheet into close contact with a cooling roll after melt extrusion.
[0138] The third step includes stretching the sheet in the machine direction and the transverse direction, and after the stretching, a heat setting step may be further included.
[0139] The stretching may be biaxial stretching or sequential biaxial stretching, and may include a step of stretching 2 to 4 times in the machine direction (MD) at 40 to 100°C after preheating to 50 to 80°C, and a step of stretching 3 to 6 times in the transverse direction (TD) at 50 to 150°C.
[0140] The heat setting step may be carried out at 50°C to 150°C, 70°C to 150°C, 100°C to 150°C, or 110°C to 140°C.
[0141] Through the stretching and heat setting, the polyester film can have improved mechanical strength and dimensional stability while maintaining a small thickness.
[0142] packaging material A packaging material according to another embodiment includes the above-mentioned polyester film. A detailed description of the polyester film is omitted since it is the same as the above-mentioned description.
[0143] The packaging material may be, for example, a disposable packaging material, a food packaging material, etc., and the polyester film may be used as is, or may further include an aluminum foil, a color layer, etc.
[0144] The packaging material is environmentally friendly because it uses biodegradable resin, which reduces the problem of carbon dioxide generation and is almost completely biodegradable under certain conditions. In addition, while using polylactic acid resin, which is currently being researched as a biodegradable film, it reduces noise levels, maintains mechanical strength at a certain level, and ensures a suitable haze value, making it highly usable as a packaging material.
[0145] The following examples are merely illustrative and are not intended to limit the scope of the present invention.
[0146] 1. Preparation of polyester films of Examples 1 and 2 The first resin composition was a mixed resin of 93.9 parts by weight of a polylactic acid polymer, 6 parts by weight of a polyhydroxyalkanoate polymer, and 0.1 parts by weight of calcium carbonate, based on 100 parts by weight of the first resin.
[0147] In the first resin, the polylactic acid polymer has a D-lactide content of about 1 to about 3 mol % and a melt viscosity of about 7,000 to about 12,000 P (poise) at 210 degrees Celsius, the polyhydroxyalkanoate polymer has a 4HB content of 30 to 35 mol %, and the calcium carbonate particles have a D50 of 1.5 μm.
[0148] As the second resin, 100 parts by weight of polybutylene adipate co-terephthalate resin having a melt viscosity of about 4,000 to about 7,000 P (poise) at 210 degrees Celsius and an aliphatic component content of 50 mol% in the acid component was used.
[0149] The first resin was dried in a dehumidifying dryer at 60 degrees Celsius for 8 hours or more, and the second resin was dried in a dehumidifying dryer at 80 degrees Celsius for 2 hours or more to remove moisture.
[0150] Using two extruders and a multi-layer feed block in which layers are alternately stacked with a preset number of layers, the first resin was melt extruded in an extruder with a temperature of 210° C., and the second resin was melt extruded in an extruder with a temperature of 210° C. The ratio (volume ratio) of the output rate of the first resin to the second resin was applied at 70:30.
[0151] In the multi-layer feed block, the first resin composition was branched into 36 layers, and the second resin composition was branched into 36 layers, and then alternately laminated, so that the first and second layers were laminated in 72 layers, and the outermost layers on the upper and lower surfaces were each provided with a skin layer at about 10% of the total thickness, and the skin layer was applied with the first resin composition and had the same composition as the first layer. After that, the sheet was passed through a 780 mm die and then brought into contact with a cooling roll cooled to 20 degrees Celsius to obtain an unstretched multi-layer sheet of 73 layers including the outermost layer (the portion where the skin layer and the first layer are adjacent was treated as one layer).
[0152] The unstretched multilayer sheet was stretched 3.0 times in the longitudinal direction at 65 degrees Celsius and 4.0 times in the transverse direction at 85 degrees Celsius, and then heat-set at 120 degrees Celsius with a relaxation rate of 1% to produce a 20 μm biaxially stretched multilayer film (Example 1).
[0153] Example 2 was prepared similarly to Example 1, but with a thickness of 25 μm after stretching and heat setting.
[0154] 2. Production of polyester films in Examples 3 to 5 In Example 3, the first resin composition and the second resin composition were applied in the same manner as above, but the ratio (volume ratio) of the discharge amounts of the first resin composition and the second resin composition was 50:50.
[0155] Within the multi-layer feed block, the first resin composition was branched into 36 layers and the second resin composition was branched into 36 layers, which were then alternately laminated, resulting in 72 layers of the first and second layers each.The outermost layers on the upper and lower surfaces each had a skin layer, approximately 8% of the total thickness, and the first resin composition was applied to the skin layer, so that it had the same composition as the first layer.
[0156] Other procedures were applied in the same manner as in Example 1 to produce a 20 μm biaxially stretched multi-layer film (Example 3).
[0157] Example 4 was carried out in the same manner as in Example 3 to produce a biaxially stretched multi-layer film of 25 μm.
[0158] In Example 5, the first resin composition was branched into 15 layers and the second resin composition was branched into 15 layers and laminated alternately in a multi-layer feed block, resulting in 30 layers of the first and second layers, with skin layers positioned on the outermost layers of the upper and lower surfaces, respectively, and the first resin composition was applied to the skin layers, which had the same composition as the first layer. A total of 31 layers of film were produced, with a film thickness of 20 μm.
[0159] 3. Production of polyester films of Comparative Examples 1 to 4 In Comparative Example 1, a polylactic acid-based polymer having a D-lactide content of about 1% to about 3 mol% and a melt viscosity of about 7,000 to about 12,000 P at 210°C was used. The polymer was dried in a dehumidifying dryer at 80°C for 6 hours to remove moisture. The resin of the first resin layer was melt-extruded in an extruder at a temperature of 210°C. After passing through a 780 mm die, the polymer was brought into contact with a cooling roll cooled to 20°C to obtain a single-layer unstretched sheet. The single-layer unstretched sheet thus obtained was stretched 3.0 times in the longitudinal direction at 65°C and 3.8 times in the transverse direction at 85°C, and then heat-set at 120°C and relaxed at about 1% to produce a biaxially stretched single-layer film of about 20 μm.
[0160] In Comparative Example 2, 80% by weight of the polylactic acid polymer used in Example 1 and 20% by weight of the second resin were blended and blended in a twin-screw extruder at 200° C. This was dried in a dehumidifying dryer at 60° C. for 8 hours, and then melt-extruded at about 210° C. to produce a 30 μm single-layer unstretched sheet. This unstretched sheet was used as the film of Comparative Example 2.
[0161] In Comparative Example 3, 10% by weight of polyhydroxyalkanoate and 90% by weight of the polylactic acid polymer used in the first resin were hand-mixed, then blended in a twin-screw extruder at 200°C, processed into chips, and dried in a dehumidifying dryer at 60°C for 8 hours or more. Then, the mixture was melt-extruded in a single extruder at a temperature of 210°C, passed through a 780 mm die, and then adhered to a cooling roll cooled to 20°C to obtain a single-layer unstretched sheet. The single-layer unstretched sheet thus obtained was stretched 3.0 times in the longitudinal direction at 65°C and 3.8 times in the transverse direction at 85°C, and then heat-set at 120°C and relaxed at about 1% to produce a biaxially stretched multilayer film of about 20 μm.
[0162] In Comparative Example 4, a polylactic acid-based polymer having a D-lactide content of about 1 to 3 mol% and a melt viscosity of about 7,000 to 12,000 P at 210 degrees Celsius was used as the resin for the first layer, and a PBAT resin having a melt viscosity of about 4,000 to 7,000 P at 210 degrees Celsius and a content of aliphatic components in the acid components of 50 mol% was used as the resin for the second layer. The resin for the first layer was dried in a dehumidifying dryer at 60 degrees Celsius for 8 hours or more, and the resin for the second layer was dried in a dehumidifying dryer at 80 degrees Celsius for 2 hours or more to remove moisture. Using two extruders and a multi-layer feed block in which two layers are alternately laminated, the resin for the first layer was melt-extruded in an extruder having a temperature of 210 degrees Celsius, and the resin for the second layer was melt-extruded in an extruder having a temperature of 210 degrees Celsius. The ratio (volume ratio) of the discharge amount of the resin for the first layer to the resin for the second layer was applied at 70:30. In the multilayer feed block, the resin for the first layer was split into 36 layers, and the resin for the second layer was split into 36 layers, and the resin for the first layer and the resin for the second layer were alternately laminated, so that the resin for the first layer was arranged in the outermost layer on the upper and lower surfaces at a thickness of about 20% of the total thickness. After that, it was passed through a 780 mm die and then adhered to a cooling roll cooled to 20 degrees Celsius to obtain an unstretched multilayer sheet with 73 layers including the outermost layer (the portion where the first layer and the skin layer are in direct contact with each other is treated as one layer without layer division). The unstretched multilayer sheet thus obtained was stretched 3.0 times in the longitudinal direction at 65 degrees Celsius and 4.0 times in the transverse direction at 85 degrees Celsius, and then heat-set at 120 degrees Celsius and relaxed at 1% to produce a biaxially stretched multilayer film of 20 μm.
[0163] 4. Evaluation of physical properties Evaluation of film noise level A film cut to A4 size (210mm x 297mm) was prepared in a 650(W) x 450(D) x 500(H)mm polycarbonate box, and a digital noise analyzer (model name: CR-162C) made by Cirrus Research PLC was placed in the box. The noise analyzer was placed about 10cm away from the prepared film, and both ends of the film were held by a jig, rotated 180 degrees, and 800 RPM was used to generate noise for more than 30 seconds to measure the noise. The data was analyzed using the equivalent sound level and sound level by frequency mode of the NoiseTools Software program. The program was used to evaluate the sound level and equivalent sound level for 30 seconds at specific frequencies, and the results are shown in the table below.
[0164] Mechanical properties evaluation After preparing a film test piece according to ASTM D882, cut it to a length of 150 mm and a width of 15 mm, and then mount it so that the distance between the chucks is 50 mm. The test piece is subjected to a tensile test at a tensile speed of 200 mm / min using an Instron 5566A tensile tester. The slope of the straight line from the measurement start point to the point where the elongation rate reaches 3% is taken as Young's modulus (kgf / mm 2 ) was measured.
[0165] Tensile strength is the maximum strength when pulled (kgf / mm 2 ) and elongation was the ratio (%) of the elongation at the time of breaking of the sample to the initial elongation, and was measured using the same equipment.
[0166] Hayes The haze was measured using a Nihon Seimitsu Kogaku haze meter (model: SEP-H) in accordance with the ASTM D1003 standard.
[0167] The measurement results are summarized in Tables 1 and 2 below.
[0168] [Table 1]
[0169] [Table 2]
[0170] Comparative Example 1 is a film using only PLA, and it was confirmed that it has an equivalent sound level of 80 dB or more, which is somewhat noisy. The Young's modulus value was also relatively large, and the flexibility of the film was somewhat reduced.
[0171] Unlike Comparative Example 1, Comparative Example 2 is a film using a resin blended with PLA and PBAT, and although the flexibility was improved, the equivalent sound intensity still remained at 80 dB, which caused loud noise and a large increase in the Bayesian value. This is believed to be due to the poor compatibility of the two resins.
[0172] Comparative Example 3 is a film using a resin in which PLA is blended with PHA, and the Young's modulus is 300 kgf / mm 2 As described above, the system was evaluated as being somewhat insufficiently flexible and its Bayes value was also large.
[0173] Unlike Comparative Example 3, Comparative Example 4 is a film using an alternating laminate structure of PLA and PBAT without blending PHA into PLA, and has a lower haze value than the other Comparative Examples, which is advantageous in terms of light transmittance, but still has a high equivalent noise intensity and Young's modulus.
[0174] In the case of the examples, it was confirmed that the equivalent noise intensity of the film tended to be lower, and the Bayes value was low.
[0175] In Examples 1 to 5, each of the polyester films had an equivalent noise intensity of 80 dB or less and a Young's modulus of 300 kgf / mm 2 At the same time, it was confirmed that Bayes did not exceed 10%.
[0176] The resins in the examples and comparative examples were all made of biodegradable resins, and in addition to having biodegradable properties, they reduced the noise level, which was a drawback of existing biodegradable resin films, improving their usability as packaging materials, etc.
[0177] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the appended claims also fall within the scope of the present invention. [Explanation of symbols]
[0178] 100 Polyester film 50 Laminate 52 1st layer 54 2nd layer 70 Skin Layer 10 Bar 12 Fixed part 14 Noise Analyzer d Distance
Claims
1. A polyester film comprising a laminate of a first layer containing a polylactic acid-based resin and a second layer containing a terephthalate residue and an adipic acid residue, the first layer being alternately laminated with the second layer, The first layer contains 1 to 7 parts by weight of the polyhydroxyalkanoate resin based on 100 parts by weight of the polylactic acid resin, The laminate is formed by alternately laminating the first layer and the second layer in 30 or more layers, The polyester film has an average equivalent noise intensity of 78 dB or less in an evaluation of film noise intensity by applying a 180 degree rotation at 800 rpm for 30 seconds or more, and a Young's modulus of 280 kgf / mm 2 The following is a polyester film.
2. 2. The polyester film according to claim 1, which has a noise level of 63 dB or less at 250 Hz in an evaluation of a noise level of the polyester film when the laminate has a thickness of 16 μm.
3. The polyester film according to claim 1 , wherein the polyester film has a haze of 10% or less.
4. 2. The polyester film according to claim 1, which has a noise level of 53 dB or less at 500 Hz when the laminate has a thickness of 16 μm and is evaluated for noise level of the polyester film.
5. 10. The polyester film of claim 1, wherein the second layer comprises a polybutylene adipate co-terephthalate resin.
6. 2. The polyester film according to claim 1, wherein the thickness ratio of the first layer to the second layer is 1:0.2-1.
5.
7. The polyester film further comprises a skin layer, The skin layers are disposed on one side and the other side of the laminate, The polyester film according to claim 1 , wherein the skin layer comprises a first resin including a polylactic acid-based resin and inorganic particles.
8. A polyester film comprising a laminate in which a first layer containing a polylactic acid-based resin and a second layer containing a terephthalate residue and an adipic acid residue are alternately laminated in 30 or more layers, the first layer contains 1 to 7 parts by weight of the polyhydroxyalkanoate resin based on 100 parts by weight of the polylactic acid-based resin, and the polyester film has a noise level of 80 dB or less at 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, 4000 Hz and 8000 Hz when the film noise level is evaluated by applying a 180 degree rotation at 800 rpm for 30 seconds or more.
9. A packaging material comprising the polyester film of claim 1.
Citation Information
Patent Citations
Polylactic acid-based oriented film
JP2013147580A
Multilayer biodegradable film
JP2013541447A
Film containing polylactic acid-based resin
JP2016043650A